Rehousing older social housing tenants: a mixed-methods study. (November 2021) - Scott, Hannah; Mattocks, Calum; Blank, Lindsay; Buckner, Stefanie
Abstract: Background: In the context of a social housing crisis, partly caused by insufficient affordable homes, the UK must meet the housing needs of an ageing population. Rehousing schemes run by social housing providers are an important means to support older (>55 years) tenants to move to appropriate homes. Hackney Council (London, UK) runs or supports many of these schemes. This study aims to assess how well the schemes are working by exploring the processes involved and their health-related outcomes. Methods: In this mixed-methods study, we interviewed practice-based stakeholders who work across four rehousing schemes in Hackney. A postal survey was delivered to older social housing tenants who had moved through one of the schemes. Responses to the survey questions were analysed in Excel. A photovoice component (ie, photographs taken by participants that were discussed in interviews and focus groups) of survey respondents captured their experiences of being rehoused and its health-related effects. Written consent was obtained from all participants. Ethical approval was obtained from the Ethics Committee of the University of Cambridge School of the Humanities and Social Sciences. Findings: Since June 4, 2020, we interviewed 14 practice-based stakeholders and surveyed 798 older tenants. We had 75 (9·4%) valid responses, of which 31 respondents were women, 10 were men, and two preferred not to say (there was missing data for 32 respondents). 16 survey respondents then participated in the photovoice group. Interviews with practice-based stakeholders were analysed using NVivo (version 12) and highlighted the importance of providing personalised support to tenants. Several outcomes were reported by stakeholders, including increased social connectedness, and improved tenant wellbeing. Challenges included there being insufficient suitable homes for tenants to move into, and problems posed by COVID-19. The survey identified positive elements (eg, being given choices) and challenges (eg, poor communication) in the rehousing process. It also identified beneficial outcomes (eg, having a warmer home without stairs) and unwelcome outcomes (eg, increased loneliness). The photovoice component and data collection with non-movers provided detailed additional insights, some captured in visual material (eg, one tenant described the community activism that had led to the restoration of an old football pitch on the site). Interpretation: The findings will inform efforts by social housing providers to optimise the rehousing experiences of older social housing tenants and maximise health-related outcomes. This will be achieved through extensive engagement with practice-based stakeholders, including through an end-of-project photovoice exhibition and a national stakeholder workshop. Funding: NIHR School for Public Health Research.